Psychological health and discrimination experience among graduate students: findings from the Stress Coping Obstruction Prevention & Education (SCOPE) Study. Issue 3 (9th September 2014) - L. Wilkinson, Larrell; Kerr, Jelani; Smith, Temple; Salaam, Muhammad; W. Flournoy, Minnjuan; Magwood, Jametta; Williams, Edith; Glover, Saundra
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – African-Americans historically report greater exposure to discrimination and also experience unfavorable outcomes associated with physical health, poverty concentration, residential segregation, and poorer education. The effects of discrimination are particularly harmful on mental health as discriminatory experiences contribute significantly to diminished mental health status and psychological distress. African-Americans pursuing graduate education may experience additional stressors, increasing the risk for poorer mental health. The purpose of this paper is to examine the association of psychological health and discrimination experiences among black and white graduate students at a southeastern university. Design/methodology/approach – Participants were 505 graduate students at a predominantly white southeastern institution. Researchers collected data via self-administered online and paper questionnaires during the spring 2010 semester. Graduate students were asked questions pertaining to individual demographics, discrimination, and psychosocial concerns. Findings – Approximately 15 percent of the graduate students reported psychological distress. Additionally, black graduate students reported significantly higher levels of day-to-day and lifetime discrimination when compared to white graduate students. In addition to the proportions of psychological distress differing by race, African-American graduate students reported better psychological well-being when exposed to both day-to-day and lifetime discrimination than whites with similar exposure. Practical implications – Resilience factors and coping strategies should be examined further among African-American graduate students for greater understanding. Moreover, it is important to develop applications to improve mental health outcomes for all graduate students. Originality/value – This is one of the few studies to focus on the mental health and discrimination experiences among a graduate student population. The sample is drawn from the southeastern USA where there are long vestiges of discrimination and a sizable sampling of African-Americans who live in the USA.